Increased NIH 3T3 fibroblast functions on cell culture dishes which mimic the nanometer fibers of natural tissues - Bhardwaj G (Dove Medical Press, 2015)
Garima Bhardwaj,1 Thomas J Webster1,21Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 2Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi ArabiaAbstract: Traditional flat tissue cell culture dishes have consisted of polystyrene treated with plasma gases for growing, subculturing, and studying cell behavior in vitro. However, increasingly it has been observed that mimicking natural tissue properties (such as chemistry, three-dimensional structure, mechanical properties, etc) in vitro can lead to a better correlation of in vitro to in vivo cellular functions. The following studies compared traditional NIH 3T3 fibroblasts’ functions on XanoMatrix scaffolds to standard tissue culture polystyrene. Results found significantly greater fibroblast adhesion and proliferation on XanoMatrix cell culture dishes which mimic the nanoscale geometry of natural tissue fibers with true, tortuous fiber beds creating a robust, consistent, and versatile growth platform. In this manner, this study supports that cell culture dishes which mimic features of natural tissues should be continually studied for a wide range of applications in which mimicking natural cellular functions are important.Keywords: nanotechnology, cell culture, fibroblasts